Aplikasi Gemas tentang Pencegahan Stunting terhadap Peningkatan Pengetahuan dan Sikap Ibu Hamil - Siti Mulidah; Asrin Asrin; Maisje Marlyn Kuhu (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of giving the Gemas application on stunting prevention on the knowledge and attitudes of pregnant women. The method used is experimental with a control group pretest and posttest design. The results showed that there were changes in the knowledge and attitudes of respondents in the significant category where the significance value was <Î± (0.05) so that it could be interpreted that statistically, there were differences in the importance of knowledge and attitudes of pregnant women before and after treatment in both the intervention and control groups. In conclusion, efforts to increase knowledge and attitudes can be carried out using smartphone-based media because it is more practical and easily accessible, and almost everyone currently has these devices. Keywords: Gemas Application, Pregnant Women. Knowledge, Attitude